KARAKTERISASI SENSOR POLIMER KONDUKTIF POLIANILIN BERPENGISI SERBUK BAN UNTUK MENDETEKSI KONDUKTIVITAS MINYAK - Rizky Dharmawan; Satriaji Sudigdo; Hamidah Harahap (Talenta Publisher (Universitas Sumatera Utara), 2014)
Conductive polymer sensor with varying amounts of poly aniline and tire dust and 1.4-methyl-pyrrolidinone as solvent using polymerization process have been developed. The polymerization process was prepared at temperature 100o C in the boiling water at 30 minutes. Conductive polymer sensor¬ is undergone several type of the analysis including electrical conductivity, Scanning Electron Microscope, Fourier Transform Infra-Red (FTIR), X-Ray Diffraction (XRD). The test used some kind of oil (palm oil, corn oil, diesel oil, and engine oil). The result showed that the highest electrical conductivity for the sensor-4 (20 per hundred resin of the tire dust) at 80oC for 30 minutes. Scanning electron microscope result shows rough surface and well dispersed of the tire dust in poly aniline / tire dust conductive blends. The analysis of X-RD shows the face center cubic (FCC) crystallographic structure of the sensor. The optimum of the electrical conductivity of the sensor was applied to detect the palm oil. The sensor given response towards palm oil (Neptune) compered to corn oil, diesel oil, and engine oil.